Stereoselective synthesis of 4-oxo-2,5-dienes and conjugated dienes by Stille cross coupling reactions of vinylstannanes - Fidelibus, Pablo Martin (2007)
The palladium-catalyzed cross coupling reactions between trineophylstannylvinyl esters and unsaturated acyl chlorides lead mostly to 4-oxo-2,5-dienes in good yields (60-77%). In some cases homocoupling products are also formed. On the other hand, the Stille reaction of Z-di- and trisubstituted vinyl iodides with trineophylvinylstannanes enables the synthesis of polysubstituted butadienes in moderate to good yields (40-60%).